2014
DOI: 10.4269/ajtmh.13-0737
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cutaneous Leishmaniasis in an Endemic Region in India

Abstract: Abstract. Cutaneous leishmaniasis (CL) is endemic in the Bikaner region situated in the Thar Desert of Rajasthan, India. This study describes clinicoepidemiological data of pediatric CL in pre-school children (0-5 years of age) from this region during 2001-2012. In total, 151 patients with 217 lesions were reported during the study period. The mean age of the study group was 3.29 ± 1.43 years (0.25-5 years), with many (41.7%) cases being in the age group of 2-4 years. Face was the most common site involved, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 17 publications
5
27
2
Order By: Relevance
“…Dry type CL lesions were common in this study group, in agreement with previous studies conducted in Sri Lanka [12], India [30], Libya [31], and in Syria [32]. However, females had more wet lesions than males.…”
Section: Discussionsupporting
confidence: 91%
“…Dry type CL lesions were common in this study group, in agreement with previous studies conducted in Sri Lanka [12], India [30], Libya [31], and in Syria [32]. However, females had more wet lesions than males.…”
Section: Discussionsupporting
confidence: 91%
“…11 Higher predilection in this age group can be explained by frequent outdoor activities (school going, outdoor playing activities) thus making them prone to bites by infected vectors. Authors found a male to female ratio of 1.88 similar to studies by Agrawal, Bari and Shoaib et al 8,11,13 The lesions were most frequently seen on the face and neck (86.09%) in accordance with studies by Aksoy et al and Agrawal et al 6,8 Face was the most commonly affected site in 80.87% cases in accordance with study by Zaraa et al 14 Although a single lesion was most commonly observed, multiple lesions (more than one) were not uncommon. Bari et al observed multiple lesions in 25% of cases, which was similar to the finding in present study (27.8%).…”
Section: Discussionsupporting
confidence: 84%
“…In children face being the most unprotected and exposed, is the commonest site for sand-fly bite. 8 Although CL is selflimiting and does not cause mortality, but it causes cosmetic disfiguration, persistence and spread into mucocutaneous form thus increases expenses on treatment and side effects of available drugs. 9 Therefore, treatment is recommended to prevent these complications especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…In India, a single lesion (72.2%) was most frequently detected in the 0-5 age group of patients. The authors reported that 19.9% of patients had two lesions and 7.9% of patients had multiple lesions [17]. In another study from Iran, only one lesion was detected in 82.3% of patients, two lesions were detected in 12.4% of patients, and ≥ 3 lesions were detected in 5.3% of patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting result of our study is that in 63.6% (n = 7) of patients with ulcer type the lesions occurred on extremities. When other studies were reviewed, it was observed that papules [14], plaques [16], plaques or papulonodules [17] or ulcers [10] were reported as the most common types of lesions.…”
Section: Discussionmentioning
confidence: 99%